Targeted Recombination within the Spike Gene of Murine Coronavirus Mouse Hepatitis Virus-A59: Q159 Is a Determinant of Hepatotropism - Leparc-Goffart, Isabelle (American Society for Microbiology, 1998)
Previous studies of a group of mutants of the murine coronavirus mouse hepatitis virus (MHV)-A59, isolated from persistently infected glial cells, have shown a strong correlation between a Q159L amino acid substitution in the S1 subunit of the spike gene and a loss in the ability to induce hepatitis and demyelination. To determine if Q159L alone is sufficient to cause these altered pathogenic properties, targeted RNA recombination was used to introduce a Q159L amino acid substitution into the spike gene of MHV-A59. Recombination was carried out between the genome of a temperature-sensitive mutant of MHV-A59 (Alb4) and RNA transcribed from a plasmid (pFV1) containing the spike gene as well as downstream regions, through the 3′ end, of the MHV-A59 genome. We have selected and characterized two recombinant viruses containing Q159L. These recombinant viruses (159R36 and 159R40) replicate in the brains of C57BL/6 mice and induce encephalitis to a similar extent as wild-type MHV-A59. However, they exhibit a markedly reduced ability to replicate in the liver or produce hepatitis compared to wild-type MHV-A59. These viruses also exhibit reduced virulence and reduced demyelination. A recombinant virus containing the wild-type MHV-A59 spike gene, wtR10, behaved essentially like wild-type MHV-A59. This is the first report of the isolation of recombinant viruses containing a site-directed mutation, encoding an amino acid substitution, within the spike gene of any coronavirus. This technology will allow us to begin to map the molecular determinants of pathogenesis within the spike glycoprotein.